2009
DOI: 10.1037/a0017095
|View full text |Cite
|
Sign up to set email alerts
|

Emotional attention set-shifting and its relationship to anxiety and emotion regulation.

Abstract: Attentional deployment is a primary strategy individuals use to regulate emotion. In 2 experiments, a measure of an individual's ability to deploy attention toward and away from emotional mental representations was developed. This measure of attentional control capacity for emotion adapted an explicit-cuing task switching paradigm in which participants had to shift between emotional and neutral mental sets. Experiment 1 (N = 118) showed that those higher in trait anxiety and worrisome thoughts took longer to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 60 publications
(97 reference statements)
4
79
0
1
Order By: Relevance
“…Likewise, further research is needed to examine additional parental characteristics, such as beliefs and worries about child pain [see e.g., 34], and their role in understanding nature and consequences of emotion regulatory strategies. Finally, the present study compares two attentional strategies and thus does not reflect the broadness and complexity of the emotion regulation repertoire, including the key ability to flexibly switch between different strategies [1,47,84]. Within-subject designs lacking specific instructions regarding strategy implementation would yield important information about parents' spontaneous strategy choice, ability to flexibly switch between strategies, and the impact of these factors on emotion and helping behavior.…”
Section: Discussion (Word Limit: 1500 / Word Count: 1494)mentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, further research is needed to examine additional parental characteristics, such as beliefs and worries about child pain [see e.g., 34], and their role in understanding nature and consequences of emotion regulatory strategies. Finally, the present study compares two attentional strategies and thus does not reflect the broadness and complexity of the emotion regulation repertoire, including the key ability to flexibly switch between different strategies [1,47,84]. Within-subject designs lacking specific instructions regarding strategy implementation would yield important information about parents' spontaneous strategy choice, ability to flexibly switch between strategies, and the impact of these factors on emotion and helping behavior.…”
Section: Discussion (Word Limit: 1500 / Word Count: 1494)mentioning
confidence: 99%
“…Gross' process model of emotion generation/regulation [39] suggests an explanation by differentiating two types of regulation strategies, defined by timing and role during the unfolding of an emotional response. According to Gross [39], attentional strategies (e.g., attentional engagement vs. avoidance) can be considered antecedent-focused in that they operate before or during emotional activation rather than after emotion has achieved full form [39,47,48]. In contrast, response-focused strategies reflect attempts to control ongoing emotional (i.e., physiological, experiential, behavioural) responding.…”
Section: Discussion (Word Limit: 1500 / Word Count: 1494)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gross and Thompson's [2007] modal model of ER is one commonly employed framework for guiding the selection of measures and operationalizing ER for research and clinical purposes Bilek & Ehrenreich-May, 2012;Campbell-Sills & Barlow, 2007;Johnson, 2009]. It has been used as the basis for advancing the development of cognitive behavioral interventions for youth [Ehrenreich-May, Queen, Bilek, Remmes, & Marciel, 2013;Trosper et al, 2009] and for adults [Moses & Barlow, 2006].…”
Section: Modal Model Of Ermentioning
confidence: 99%
“…In line with this, some studies show a decrease in physiological arousal during meditation (Danucalov, Simões, Kozasa, & Leite, 2008;Telles, Mohapatra, & Naveen, 2005) and a concomitant effect of a relaxed state with an attentive mind during practice (Kubota et al, 2001;Takahashi et al, 2005;). This can be particularly important because some studies demonstrated that high levels of anxiety can interact with attention, impairing the cognitive modulation of negative emotion (Johnson, 2009;Mocaiber et al, 2009).…”
Section: Sitting and Silent Meditationmentioning
confidence: 99%